Strategic Applications for Construction Management Enhancement - Waheed, Muhammad; Mutahir Abbas (RADINKA JAYA UTAMA PUBLISHER, 2023)
This software application brings new ideas in the development of applications and helps small businesses complete the business process on time. It is designed to monitor applications, work management, problem lists, and transfer of work or information by electronic means, which is very important in Android, iOS and PC mode. Special applications provide users with useful functions such as receiving instructions from the web, sending explanations, storing work-related information, etc. This client work includes office-to-employee and employee-to-employer relationships. The ultimate goal of the app is to be a bridge between employees and employers for monitoring, updating, monitoring and optimization. Discussion and explanation of a successful application can play an important role in developing it.